Smart materials and structures: fantasy or reality? - Yurlova, N. A. (Perm Federal Research Centre Journal, 2013)
The article is devoted to the new interdisciplinary field of continuum mechanics – smart- materials and structures: the history of their appearance, particularities of their establishment and the way they work, opportunities for practical use.